MORPHOLOGICAL MARKERS OF VERB MODALITY IN JAVANESE SURABAYA DIALECT - ZULFERDI, LAZUAR AZMI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Zulferdi, Lazuar Azmi. 2013.  Morphological Markers of Verb Modality in Javanese Surabaya Dialect. Study Program of English, Universitas Brawijaya. Supervisor: Eni Maharsi; Co-Supervisor: Yana Shanti Manipuspika.   Keywords: Dialect, Javanese Language, Verb Modality, Morphological Markers, Surabaya Dialect   Dialect is a variety of a language that has  unique patterns of phonology, morphology, syntax, and vocabulary. Dialect  is spoken and understood by a particular language society. One of  dialects  in Indonesia is Javanese Surabaya Dialect  (JSD). The uniqueness of  JSD  can be seen through its morphology and verb modality. Thus, this study was conducted to describe  the characteristics of morphological marker and the use of verb modality in JSD. This  study used a qualitative approach. The data are verbs which contain morphological markers that characterize Javanese Surabaya dialect. In collecting the data, Stimulating Technique or Teknik Pancing and structured interview were employed. In data  analysis,  the data  were put into  tables  in accordance with morphological markers identified  from the verbs. Further explanations according to  the morphological markers and verb modality theory become part of the analysis. The results of this study  revealed that there were 72  inflected verbs  in Javanese Surabaya dialect taken from 12 base verbs of standard Javanese. Most of the inflected verbs have similar characteristics with the morphological markers in standard Javanese. However, there were two morphological markers which were not in the category of standard one. They reveal the uniqueness of morphological markers in Javanese Surabaya dialect.  In  addition,  three types of verb modality occurred most often in the daily communication of native speaker of JSD were found. They are indicative, imperative, and subjunctive optative.  In conclusion,  the characteristics of  Javanese Surabaya dialect share  a major similarity and minor difference with the morphological markers in standard Javanese. It has  uniqueness in the morphological markers used in some of the words. For further research in dialect, it is suggested that the next writers who are interested in  Javanese Surabaya dialect  to analyze it from phonological and syntactical point of view.